GENDER EQUALITY ISSUES IN DISNEY’S MOVIE “MULAN (2020)” - Ramadhani, Hanindya; Alida, Rizky; Permatasari, Fitriya Desita; Utami, Silvi Diah; Safala, Desinta Vanesti (Fakultas Ilmu Budaya, Universitas Mulawarman, 2022)
ABSTRACT Gender equality is defined as a thought that men and women have equal rights as human beings and should be treated equally. This issue becomes interesting to discuss because not all women and girls around the world experience equal rights. Mulan (2020) is a movie that shows the problem of gender equality. This research aims to point out that Mulan (2020) is considered as a movie depicting issues against women and a main character's effort to fight for human rights and achieve gender equality by analyzing scenes and dialogues. The research used descriptive study with a qualitative approach as a method of research. The semiotics analysis of Charles Sanders Peirce and liberal feminism theory used as the ground of knowledge to support the research. The results found in this research indicate that gender equality in this movie is a part of culture that includes physical and verbal form. The amount of research data analyzed consists of 10 data in the form of pictures and dialogues. In addition, this movie is shown to achieve the same rights, especially for women who often lose their rights as a result of society's demands and norms. Keywords: Movie, Semiotics Charles Sanders Peirce, Gender Equality, Chinese Culture